A análise do empreendedorismo social e ações contra o racismo e injustiça ambiental - Quadros, Liziane Janaína (Universidade do Vale do Rio dos Sinos, 2021)
This monograph aims to analyze the practices and actions of Ambiafro's social entrepreneurship, whether or not to combat environmental and structural racism, and to understand the naturalization of inequalities through these same racisms in Brazil. The research methods used are bibliographical, in-depth semi-structured interviews and document analysis. From this perspective, a historical reconstruction and a systematic analysis of structural and environmental racism were carried out. Likewise, it was analyzed, based on the referred laws aimed at facing inequalities, how and which actions of the Ambiafro social enterprise could alleviate or solve the problem that occurs against the black population. Upon analyzing the problem, it is evident that these social enterprises see themselves as promoters of anti-racism, placing the issue at the center of the debate and then planning actions and practices to combat racism.
Keywords: Empreendedorismo social; Racismo estrutural; Racismo ambiental; População negra; Social entrepreneurships; Structural racism; Environmental racism; Black population